Instagram Reels as a Digital Tool for Business-to-Business Engagement - Lolita, Theresia Lavietha Vivrie (Jurnal ILMU KOMUNIKASI, 2025)
This study examines Instagram Reels' potential as a strategic digital tool for B2B marketing objectives, addressing the under-researched application of short-form video platforms in organizational contexts. The research synthesizes contemporary literature on B2B marketing frameworks and Instagram's dynamic feature evolution through qualitative narrative methodology. Findings identify optimal content strategies, including brand narrative development, educational dissemination, cultural demonstration, and product teasers that align with B2B commercial imperatives. The analysis establishes Reels' capacity to enhance brand visibility, audience engagement, and market positioning while proposing actionable methodologies for integrating ephemeral video content into omnichannel marketing architectures.